The determinants and treatments of shariah non- compliant events in Malaysian Islamic banks - Mohd Yunus, Saidatolakma; Mohd Noor, Azman; Kamaruddin, Zuraidah; Embong, Rahimah (2023)
This article delineates the concept of Shariʻāh non-compliant events (SNEs) in Malaysian Islamic Banks, its determinants and treatments fromthe Islamic perspective based onMuslim scholars' discussion. This research is qualitative, and it utilises textual analysis technique in analysing the data. Its findings argue that SNEs occur in almost all Malaysian Islamic Banks due to factors like human errors and pressing needs. Furthermore, the research reveals that the treatment undertaken by the banks is rectification and re-execution but different from one Islamic bank to another. This article argues that the existing approach to SNEs could be improved, enriched and possibly standardised.